Feasibility Study of a Low Cost Saltwater Lamp for Rural Area - Bani, Nurul Aini; Hassan, Mohamad Zaki; Mad Kaidi, Hazilah; Muhtazaruddin, Mohd Nabil; Sarip, Shamsul; Saleh, Safiza; Mohd Izhar, Mohd Azri; Mohd Aris, Siti Armiza; Abd Jalil, Siti Zura; Mohamed Rashidi, Ahmad Hadi (International Journal of Integrated Engineering, 2018)
Renewable energy is energy generated from natural resources and cannot be depleted. Solar energy is the fastest growing source of renewable energy but the high installation and maintenance cost of a solar system has restrained the consumers from adopting this technology at their home or commercial building. This is especially true for those in developing countries. A new promising renewable energy source known as saltwater energy that takes advantage of the conductive nature of salt water to generate electricity, has intrigued many people. A study has been conducted to develop and produce saltwater-powered devices especially for rural and remote communities in Malaysia as well as worldwide. To main objective of this study is to determine the factors that affect the performance of the saltwater energy generation such as electrode’s combinations, number of cells and the durability of the electrodes. It was found that the choice of electrodes as anode and cathode does affect the voltage output. However, due to the small power produce, the number of cells must be increased to produce enough power to light up a led light and to provide power to USB port. This paper also conducted a cost analysis of using the saltwater lamp and compared it with a solar system. Although the difference in the cost per hour is very small, there are a number of disadvantages of solar system that need to be aware of. The findings obtained from these experiments will be used to design a prototype of the illumination technology for further product development.